Spectrophotometric Method for Estimation of Leflunomide in Bulk and Tablets - Rabindra Pal, N.; Chakraborty, Manas; Debnath, Rabindra; K. Gupta, Bijan (Asian Journal of Chemistry, 2010)
A simple and sensitive UV spectrophotometric method for determination of leflunomide in bulk and tablets has been developed. Beer' law is obeyed in the concentration of 8-30 mcg/mL of leflunomide. The method was found to be simple, precise, accurate and cheap for routine analysis with recovery of 99.06 ± 0.7593 %. The method does not require any separation of soluble excipient in the tablet as they do not interfere in the estimation. Results of analysis was verified statistically and by recovery studies thus the method can be used for routine, quality control of bulk and other formulations.